2009
DOI: 10.1111/j.1939-1676.2008.0216.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Isoflurane General Anesthesia or Anesthesia and Surgery on Thyroid Function Tests in Dogs

Abstract: Background: Anesthesia and surgery affect thyroid function tests in humans but have not been studied in dogs. Hypothesis: Anesthesia and anesthesia with surgery will affect thyroid function tests in dogs. Animals: Fifteen euthyroid dogs. Methods: Prospective, controlled, interventional study. Dogs were assigned to one of 3 groups: control, general anesthesia, and general anesthesia plus abdominal exploratory surgery. Dogs in the anesthesia and surgery groups were premedicated with acepromazine and morphine, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 26 publications
0
24
1
Order By: Relevance
“…In addition, it may be argued that in the present case blood for thyroid hormone tests was collected 4 days after surgery and that surgery under general anesthesia could have affected thyroid hormone measurements. However, a study on euthyroid dogs receiving abdominal surgery under general anaesthesia revealed no significant differences between the surgery and the control group regarding T4, fT4, T3, and TSH concentrations on days 1-6 post surgery [39]. Although these results cannot be directly transferred to cats and the situation in an orthopedic surgery may differ from that in soft tissue surgeries, the cited study indicates that the preceding surgical procedure may have had only limited influence on initial hormone values.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, it may be argued that in the present case blood for thyroid hormone tests was collected 4 days after surgery and that surgery under general anesthesia could have affected thyroid hormone measurements. However, a study on euthyroid dogs receiving abdominal surgery under general anaesthesia revealed no significant differences between the surgery and the control group regarding T4, fT4, T3, and TSH concentrations on days 1-6 post surgery [39]. Although these results cannot be directly transferred to cats and the situation in an orthopedic surgery may differ from that in soft tissue surgeries, the cited study indicates that the preceding surgical procedure may have had only limited influence on initial hormone values.…”
Section: Discussionmentioning
confidence: 89%
“…In veterinary medicine, the only 2 species previously tested are dogs and laboratory rats, and in both, the measured thyroid hormones serum concentration was decreased after isoflurane anesthesia. 6,27 The rats under brief anesthesia were compared with control animals, 6 and the dogs were tested over multiple time points until 338 h after procedures. 27 The prairie dogs in our study were tested at 3 time points during brief (60 min) isoflurane-only anesthesia, to assess the effect on the thyroid as a potential risk factor for this type of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…6,27 The rats under brief anesthesia were compared with control animals, 6 and the dogs were tested over multiple time points until 338 h after procedures. 27 The prairie dogs in our study were tested at 3 time points during brief (60 min) isoflurane-only anesthesia, to assess the effect on the thyroid as a potential risk factor for this type of anesthesia. Future studies should include a prolonged testing period and unanesthetized control animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations